2017
DOI: 10.1103/physreva.96.012501
|View full text |Cite
|
Sign up to set email alerts
|

Antidynamical Casimir effect as a resource for work extraction

Abstract: We consider the quantum Rabi model with external time modulation of the atomic frequency, which can be employed to create excitations from the vacuum state of the electromagnetic field as a consequence of the dynamical Casimir effect. Excitations can also be systematically subtracted from the atom-field system by suitably adjusting the modulation frequency, in the so-called antidynamical Casimir effect (ADCE). We evaluate the quantum thermodynamical work and show that a realistic out-of-equilibrium finite-time… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 97 publications
1
28
0
Order By: Relevance
“…Therefore, based on Ref. [89], one can conclude that the positive quantum work in our system can be extracted and externally controlled by the modulation parameters of the atomic collisions frequency and the mechanical spring coefficient which open a new way to the quantum thermodynamics of the DCE physics.…”
Section: B Modulating Atomic Collisions Without Mo Modulationmentioning
confidence: 75%
“…Therefore, based on Ref. [89], one can conclude that the positive quantum work in our system can be extracted and externally controlled by the modulation parameters of the atomic collisions frequency and the mechanical spring coefficient which open a new way to the quantum thermodynamics of the DCE physics.…”
Section: B Modulating Atomic Collisions Without Mo Modulationmentioning
confidence: 75%
“…where L[Ô] ≡ÔρÔ † −Ô †Ôρ /2 −ρÔ †Ô /2 is the Lindblad superoperator, κ is the cavity relaxation rate and γ k,l (γ (φ) k ) are the atomic relaxation (pure dephasing) rates. Notice that related works demonstrated that for g k,l /ω < 10 −1 and initial times this approach is a good approximation to a more rigorous microscopic model of dissipation [39,45,57]. Typical behavior of 3-photon DCE under unitary and dissipative evolutions is illustrated in Fig.…”
Section: Discussionmentioning
confidence: 82%
“…The dynamical Casimir effect, consisting in the deterministic generation of quanta from the initial vacuum field state, is an emblematic example of the quantum dynamics that can be achieved in a nonstationary cavity QED regime [18,[32][33][34][35]. Conversely, in the antidynamical Casimir effect (ADCE), photons can be coherently annihilated from a large class of nonvacuum initial states [36][37][38][39]. Besides, excitations can be deterministically transferred between the field and a far-detuned atom using the sideband transitions, as demonstrated in [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [40], for instance, we have recently demonstrated that the ADCE can be used as a resource for work extraction.…”
Section: Introductionmentioning
confidence: 99%